DEVELOPING AUDIO-VISUAL LEARNING MEDIA BASED ON VIDEO DOCUMENTARY ON TISSUE CULTURE EXPLANT OF DENDROBIUM BIGIBBUM - Mellisa, M.; Yanda, Yola Dwi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
The development of science and technology challenge teachers to pay a great effort in creating an effective media. The aim of this study was to produce audio-visual learning media based on video documentary explanation of orchid plants (Dendrobium bigibbum) on tissue culture material. This research was conducted on July 2019. This R&D used the ADDIE model without implementation phase. The data collection instruments used were validation sheets and student questionnaire responses. The data obtained were analyzed using percentage.  The evaluation results of the audiovisual learning media based on video documentary tissue culture showed that it was considered as very feasible to be used with an average percentage score of 87.50% by tissue culture expert, 91,87% by learning media expert, 91.66% by the teachers, and 94.37% by the students. The effectiveness of the learning media developed need to be ensured by conducting the implementation phase.